Linking the emotional reactions to coping: a closer look at gender differences among Israeli managers. (5th February 2008) - Kariv, Dafna
This study investigates male and female's coping strategies while encountering daily managerial stressors, by deciphering their appraisals of stressors and the emotional reactions to these appraisals, i.e., perceived stress or subjective well-being. Findings indicated that men and women managers (n = 389) differ in appraising stressors; these appraisals affected both genders' emotional reactions and then their coping strategies. Multivariate results also showed that perceived stress produced emotion-oriented coping in both gender groups. The main contribution of this study is that men and women managers manifest identical coping patterns and coping behaviour is dependent upon context rather than on gender. Implications are discussed.